2013
DOI: 10.3233/wor-121538
|View full text |Cite
|
Sign up to set email alerts
|

Movement quality and links to measures of fitness in firefighters

Abstract: BACKGROUND/OBJECTIVE: Given the possible links between movement, fitness and injury, the goal of this study was to evaluate strength, endurance, and hip range of motion (ROM) (i.e. fitness); movement quality; and age in a population of firefighters. PARTICIPANTS: Male firefighters (n = 282), all members of a major Canadian city fire department, volunteered to participate in this cross-sectional study. METHODS: Torso endurance, grip strength, pull-ups, hip ROM, movement quality (sum of 7 movement tasks graded o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
2
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 11 publications
1
17
2
1
Order By: Relevance
“…In addition, a higher level of back muscular endurance has been shown to be related to improved movement quality and functional movement. 30 Previous studies have also reported that relatively small differences in back muscular endurance were useful to identify subgroups of participants with previous, current, or future low back pain. Only 5.0 seconds separated those who reported low back pain less than a week ago from those who had low back pain more than a week ago, whereas 11.8 seconds separated those with current versus previous low back pain; 16.0 seconds distinguished those with intermittent low back pain versus no low back pain; and 17.3 seconds divided those who would experience their first episode of low back pain in the next 12 months from those who would remain symptom free.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a higher level of back muscular endurance has been shown to be related to improved movement quality and functional movement. 30 Previous studies have also reported that relatively small differences in back muscular endurance were useful to identify subgroups of participants with previous, current, or future low back pain. Only 5.0 seconds separated those who reported low back pain less than a week ago from those who had low back pain more than a week ago, whereas 11.8 seconds separated those with current versus previous low back pain; 16.0 seconds distinguished those with intermittent low back pain versus no low back pain; and 17.3 seconds divided those who would experience their first episode of low back pain in the next 12 months from those who would remain symptom free.…”
Section: Discussionmentioning
confidence: 99%
“…They reported mean external obliques activation of less than 3-4% of MVC, the rectus abdominis averaged less than 2% of MVC, and erector spinae was 2-3% of MVC (38). The rifle walk condition in the preset study had relatively close values to White and colleagues (23) walking data. The only difference was slightly higher erector spinae activity in the gear condition of the present study, which could be explained by an increase in forward lean and an increase in height of the subjects' center of mass.…”
Section: Task Typementioning
confidence: 58%
“…McGill and colleagues suggested a similar training routine with movement competency components combined with fitness training for a group of firefighters (23). While not training in gear strays from the principal of specificity, occupational movement training may decrease injuries early on, which hopefully may lead to decreased chronic injuries.…”
Section: Gear Vs No Gearmentioning
confidence: 99%
“…However, the FMS seems to be, at best, weakly associated with physical performance and movement competency. 28,30 This may because the standard FMS is not sufficiently sensitive to capture biomechanical differences which influence performance in physically rigorous activities such as soccer 15 . Instead, strength and conditioning practitioners should consider a different approach.…”
Section: Practical Applicationsmentioning
confidence: 99%